Single-Cell Antibody Sequencing in Atherosclerosis Research - Saigusa, Ryosuke; Durant, Christopher P; Suryawanshi, Vasantika; Ley, Klaus (Methods in molecular biology (Clifton, N.J.), 2022)
The transcriptomic information obtained by single cell RNA sequencing (scRNA-seq) can be supplemented by information on the cell surface phenotype by using oligonucleotide-tagged monoclonal antibodies (scAb-Seq). This is of particular importance in immune cells, where the correlation between mRNA and cell surface expression is very weak. scAb-Seq is facilitated by the availability of commercial antibodies and antibody mixes. Now panels of up to 200 antibodies are available for human and mouse cells. Proteins are detected by antibodies conjugated to a tripartite DNA sequence that contains a primer for amplification and sequencing, a unique oligonucleotide that acts as an antibody barcode and a poly(dA) sequence, simultaneously detecting extension of antibody-specific DNA sequences and cDNAs in the same poly(dT)-primed reaction. For each cell, surface protein expression is captured and sequenced along with the cell's transcriptome. Here, we list the steps needed to produce antibody sequencing data from tissue or blood cells.